Pendampingan Pada Masyarakat Tentang Pencegahan Penularan Covid-19 Di Rt 003 Rw 001 Dusun Banjarsari Desa Tegalbang Kecamatan Palang Kabupaten Tuban - Sulistyani Eka Lestari; Marwan; Minan; Muhari (Universitas Merdeka Surabaya, 2020)
Assistance to the community about preventing the transmission of Covid-19. The activity was carried out at RT 003 RW 001, Banjarsari Hamlet, Tegalbang Village, Palang District, Tuban Regency. Mentoring activities run smoothly according to what is planned in the mentoring program matrix and provide assistance. As for the implementation of community service, it went well thanks to the support and cooperation of Karang Taruna, the village administration and all village communities, and village community leaders, for assistance and provision of assistance in the form of hand sanitizers, masks and virus prevention brochures. To provide understanding and awareness to people who do not understand about the Covid 19 pandemic and government policies regarding the social restriction system Physical/Social Distancing (maintaining distance) for prevention which must be carried out, but has an impact on decreasing the community's economy.